Epitaxial growth technique for single-crystalline PbTiO3 thin film on Si substrate using an HfO2 buffer layer. (17th September 2021) - Park, Hansol; Kijima, Takeshi; Tabata, Hitoshi
Abstract: We have succeeded in obtaining thin-film single crystals of PbTiO3 (PT) piezoelectrics on a Si single crystal with a few defects in the film at the extremely low temperature of 450 °C, which was considered difficult in the past. We confirmed that the obtained thin film demonstrates dielectric characteristics (lattice constant: a = 0.3904 nm, c = 0.4159 nm; relative dielectric constant: 120), along with an extremely high residual polarization value (Pr = 85 μ C cm −2 ). A martensitic transformation in the HfO2 buffer layer plays an important role in the c-domain formation of the epitaxial PT film by an elastic lattice matching. This discovery will demonstrate a new function of HfO2 film and indicates that the system can be applied in a broad range of scenarios seeking to obtain single crystals for various functional oxide layer thin films on Si wafer substrates.